Relationship of Stress and Sleep Disorders in Faculty of Medical Students of Malahayati University during COVID-19 Pandemic - Fasya, Hasmarullah; Setiawati, Octa Reni; Husna, Ismalia; Pramesti, Woro (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2021)
Background: The World Health Organization (WHO) announced on March 11, 2020 that the disease outbreak caused by the COVID-19 coronavirus is a global pandemic. Therefore those educational institutions ranging from preschool to tertiary levels are closed for a while. Lecture activities are carried out remotely through Online applications that support lecture activities. Educators and parents are confused about accompanying their children to study at home, while students are confused or stressed by online learning methods and extensive learning with many tasks, especially during the COVID-19 pandemic. This stress can cause adverse effects, such as high blood pressure, dizziness, sadness, attention, insomnia and other sleep abnormality, hypersensitivity, depression, etc. In some cases, stress can cause a variety of discomfort. Purposes: to find out the relationship between stress and sleep disorders in the COVID-19 pandemic. Methods: The test conducted in this study is the Spearman test and quantitative type with analytic design and cross-sectional approach. The measuring instruments used were the DASS 42 questionnaire (Depression Anxiety Stress Scales 42) and the PSQI questionnaire. Results: respondents in this study were 60 respondents. The largest distribution among the stress variables was moderate stress level (40%), while the largest type of the two levels of sleep disorder is bad level (80%), and the results of the correlation analysis on the stress variable with sleep disorders obtained P=0.000 and the result of the correlation coefficient r=0.720. Conclusion: Based on the results of the Spearman test on the relationship between stress and sleep disorders, the P value was 0.000 (P0.05) indicating that there was a relationship between sleep disorders and stress, while the r value was 0.720 or positive correlation, meaning that the higher the stress level, the higher the sleep disturbance, vice versa.